Roda de choro : processos educativos na convivência entre músicos - Fiorussi, Eduardo (2012)
The objective of this research is to describe and understand the educational processes arising from the interaction between musicians in a roda de choro . Based on the experiences of the researcher, from the interaction with musicians and other musical friends in social musical practices and musical education environments, and the studies done in the research of Social Practice and Educational Processes (PPGE-UFSCar), it is presented in the discussion supported referential theory involving Paulo Freire (1992, 1995, 2007), Ernani Maria Fiori (1986), and Jorge Larrosa Bondía (2002), among others. Held together with the Chorando na Sombra, that performs rodas de choro in Campinas Brazil, ethnographic research has been the source of inspiration, using methodological procedures of participant observation, since the researcher is a musician and participates in social practices mentioned. Roda de choro is a musical manifestation, collective, where people meet to play the repertoire of Brazilian popular music. In these experiments occur dialogical exchange of glances, gestures, finally learning. From the collection of data with the research participants we have come to the conclusion that the musical learning process of choro, although presenting similarities in the processes of each musician, happens to each individual in different ways; learning processes are not linear, but they involve an individual organization that occurs from the interaction with others in rodas de choro and other social practices that involve music. This thesis also deals with other learning processes that occur from musical encounters, related to respect, fellowship, listening to others, and that most shares in coexistence with others, and are often taken for other activities of daily life.